USM THE FIRST ASEAN UNIVERSITY WITH WORLDCLASS FACILITIES FOR PRE-CLINICAL AND CLINICAL STUDIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 4 July 2016 Universiti Sains Malaysia (USM) has become the first ASEAN university to have laboratory facilities catering to both preclinical and clinical studies of worldclass standards.